Resepsi Atas Dokumentasi Opera Minangkabau Malin Nan Kondang: Suatu Kajian Penonton Teater Pemula - Mustika, Novia; Hs, Wendy; Pramayoza, Dede (Creativity And Research Theatre Journal, 2023)
The Minangkabau Opera Malin Nan Kondang combines drama, dance, music, and visual arts performances, departing from the kaba Malin Kundang, a folklore from West Sumatra about a boy named Malin who is disobedient to his mother and is cursed to turn to stone. Contrary to the kaba version, Opera Minangkabau Malin Nan Kondang tells about Malin's loyalty and sacrifice to his mother and lover, Nilam. This research treats the reception of novice audiences as a formal object intended to see responses to the structure or texture of the performance, which is witnessed through documentation. Data was collected through questionnaires, direct observation, and interview techniques. Research data analysis is directed to see three things from the novice audience, namely: (1) the horizon of expectations; (2) body reaction; and (3) the segmentation effect. Based on these three things, a general conclusion is formulated, namely the reception of the novice audience. Research shows that structural aspects (plot, characters, and themes) attract more beginner audiences than the performance's texture (atmosphere, dialogue, and spectacle, be it music, dance, costumes, make-up, or lighting). The tendency to respond more to the structure than the texture of this performance through documentation shows that for novice audiences, the story aspect is more interesting than the spectacle aspect. But at the same time, it has also been proven that this performance style, called 'Minangkabau Opera,' tends to be effective in conveying stories to novice audiencesReception Of The Documentation Of Malin Nan Kondang Minangkabau Opera : A Studies Of Beginning Theater AudienceAbstrakOpera Minangkabau Malin Nan Kondang merupakan perpaduan antara pertunjukan drama, tari, musik serta seni visual, yang berangkat dari kaba Malin Kundang, sebuah cerita rakyat dari Sumatera Barat tentang seorang anak bernama Malin yang durhaka kepada ibunya, hingga dikutuk menjadi batu. Berkebalikan dengan versi kaba itu, Opera Minangkabau Malin Nan Kondang mengisahkan tentang kesetian dan pengorbanan Malin, baik kepada Ibunya, maupun kepada kekasihnya, Nilam. Penelitian ini menjadikan resepsi penonton pemula sebagai objek formal, yang ditujukan untuk melihat tanggapan atas struktur atau tekstur pertunjukan, yang disaksikan melalui dokumentasi. Data dikumpulkan melalui teknik kuisioner, pengamatan langsung, yang diteruskan dengan teknik wawancara. Analisis data penelitian diarahkan untuk melihat tiga hal dari penonton pemula, yakni: (1) horizon harapan; (2) reaksi tubuh; dan (3) pengaruh segmentasi. Berdasarkan ketiga hal tersebut, diformulasikan suatu kesimpulan umum, yakni resepsi penonton pemula. Penelitian menunjukkan bahwa aspek struktur (alur, karakter dan tema) lebih menarik perhatian penonton pemula ketimbang tektur pertunjukan (suasana, dialog dan spektakel, baik itu musik, tarian, kostum, rias, maupun pencahayaan). Kecenderungan untuk lebih menanggapi stuktur ketimbangan tekstur pertunjukan ini melalui dokumentasi menunjukkan bahwa bagi penonton pemula aspek cerita lebih menarik perhatian ketimbang aspek tontonan. Namun pada saat yang sama, terbukti pula bahwa pihan gaya pertunjukan yang dinamakan ‘Opera Minangkabau’ ini cenderung efektif untuk menyampaikan cerita kepada penonton pemula